Genotypic variability in chrysanthemum (Dendranthema grandiflora Tzvelev) under different photoperiodic treatments - Aman, Guleria; Sita, Ram Dhiman; Meenakshi, Basoli; Nitin, Sharma; Shreedhar, Beese; Vijit, Gupta; Anjalika, Dhiman; Ali, Haidar Shah (Plant Science Today, 2026)
The floriculture industry increasingly requires chrysanthemum cultivars with diverse blooming periods to ensure reliable off-season production. Accordingly, 21 genotypes were evaluated in the year 2023 under natural and controlled photoperiodic regimes in a naturally ventilated polyhouse, using a factorial randomized block design (FRBD) with three replications. Among the genotypes, the earliest colour bud initiation (133.29 days) was recorded in UHFSChr-143, which also produced the highest number of shoots per plant (3.83). The maximum number of cut flower stems per square meter (284.38) was obtained from UHFSChr-158, while the highest number of flowers per plant (132.08) and the heaviest single flower (5.69 g) were observed in UHFSChr-158 and UHFSChr-134 respectively. Across photoperiodic regimes, higher yields were achieved under the natural photoperiod, with averages of 3.36 shoots per plant, 87.61 flowers per plant, 227.49 cut stems per square meter and a single-flower weight of 2.02 g. In contrast, the controlled photoperiod significantly advanced colour bud initiation (124.57 days) and flowering, with yields slightly lower than under natural conditions. Nonetheless, by enabling off-season production, controlled photoperiod offers a significant commercial advantage, as reduced yields can be offset by higher market prices. Overall, the study demonstrated substantial genotypic variability in growth and floral attributes. Natural photoperiod favoured vegetative growth and qualitative traits, whereas controlled photoperiod optimized flowering schedules while retaining sufficient yield levels, thereby enhancing production planning and profitability in off-season markets.